Sosialisasi Lingkungan Bersih dan Sehat Untuk Siswa Sekolah Dasar - Rahmi Agustina; Ervina Dewi; Zufahmi; Zuraida; Makawiyah; Basri (Yayasan Sagita Akademia Maju, 2026)
Clean and Healthy Living Behavior (PHBS) constitutes an essential foundation in shaping the character and long-term habits of elementary school-aged children. Based on initial observations at SD Negeri 2 Adan, Mutiara Timur District, Pidie Regency, students' understanding of waste separation and the six-step handwashing procedure recommended by health authorities still required strengthening. This community service activity aimed to improve the understanding, attitude, and skills of fifth and sixth-grade students in implementing PHBS, particularly the habit of proper handwashing and the sorting of organic and inorganic waste. The activity was carried out on February 5, 2026, involving fifth and sixth-grade students of SD Negeri 2 Adan along with their homeroom teachers. The implementation approach used was participatory and interactive, utilizing a combination of material socialization methods, light group discussions with question-and-answer sessions, visual aid demonstrations, and direct practice in rotation. The program's implementation showed a highly positive and enthusiastic response from all participants. Through the direct practice approach, students not only mastered the theory but also experienced a significant increase in psychomotor skills. The combination of theoretical socialization and direct practical experience proved effective in increasing elementary school students' knowledge, ecological awareness, and motor skills in implementing PHBS.